Dietary leonurine hydrochloride supplementation attenuates lipopolysaccharide challenge-induced intestinal inflammation and barrier dysfunction by inhibiting the NF-κB/MAPK signaling pathway in broilers - Yang, Li (J Anim Sci, 2019)
This study was performed to evaluate the beneficial effects of dietary leonurine hydrochloride (LH) supplementation on intestinal morphology and barrier integrity and further illuminate its underlying antioxidant and immunomodulatory mechanisms in lipopolysaccharide (LPS)-treated broilers. A total of 120 1-d-old male broilers (Ross 308) were assigned to 4 treatment groups with 6 replicates of 5 birds per cage. The experiment was designed in a 2 × 2 factorial arrangement with LH (0 or 120 mg/kg) and LPS (injection of saline or 1.5 mg/kg body weight) as treatments. On days 14, 16, 18, and 20 of the trial, broilers were intraperitoneally injected with LPS or physiological saline. Compared with the control group, LPS-challenged broilers showed impaired growth performance (P < 0.05) from day 15 to day 21 of the trial, increased serum diamine oxidase (DAO) and D-lactic acid (D-LA) levels coupled with reduced glutathione (GSH) content and total superoxide dismutase (T-SOD) activity (duodenal and jejunal mucosa), reduced malondialdehyde (MDA) content (duodenal, jejunal, and ileal mucosa), and compromised morphological structure of the duodenum and jejunum. Additionally, LPS challenge increased (P < 0.05) the mRNA expression of proinflammatory cytokine genes and reduced tight junction (TJ) protein expression in the jejunum. However, dietary LH prevented LPS-induced reductions in average daily gain (ADG) and average daily feed intake (ADFI) in broilers. It also alleviated LPS challenge-induced increases in serum DAO levels, MDA content (duodenal and jejunal mucosa), and jejunal crypt depth (P < 0.05) but reduced villus height, GSH content (jejunal mucosa), and T-SOD activity (duodenal and jejunal mucosa) (P < 0.05). Additionally, LH supplementation significantly downregulated the mRNA expression of nuclear factor (NF)-κB, cyclooxygenase-2 (COX-2), and proinflammatory cytokines (TNF-α, IL-1β, and IL-6) and upregulated the mRNA expression of zonula occludens-1 (ZO-1) and Occludin in the jejunal mucosa induced by LPS (P < 0.05). On the other hand, LH administration prevented LPS-induced activation of the p38, extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) mitogen-activated protein kinases (MAPKs) and attenuated IkB alpha (IκBα) phosphorylation and nuclear translocation of NF-κB (p65) in the jejunal mucosa. In conclusion, dietary LH supplementation attenuates intestinal mucosal disruption mainly by accelerating the expression of TJ proteins and inhibiting activation of the NF-κB/MAPK signaling pathway.